STATUS FISIOLOGIS TERNAK SAPI BALI (Bos sondaicus) BETINA YANG DIPELIHARA PADA LAHAN GAMBUT (Physiological Status of Bali Cattle (Bos sondaicus)Maintained on Peatlands) - K., Amiano; B., Satata; R., Imanuel (Universitas Palangka Raya, 2018)
ABSTRACTThe study aimed to determine the extent of the physiological status of Balinese cattle (Bos sondaicus) females maintained on peatlands including environmental temperature, respiratory frequency, body temperature, pulse rate, and rumination which is important to know the health status of female Balinese cattle. This study used 10 female Balinese cows with an average body weight of 300 kg and age ranged from> 24-36 months, non-pregnant status. Physiological status measurements were carried out in the morning, afternoon and evening. This study uses descriptive methods and direct observation with data processing in analysis and tabulation. Research has been carried out at the Joint Work Group of Taruna Taruna, Tanjung Taruna Village, Jabiren Raya District, Pulang Pisau Regency. The research began on January 1, 2018 to February 2, 2018. The results showed that the average cage temperature in the morning was 28.0 0C and humidity was 79.4%. While during the day the temperature of the cage is 33.8 oC and humidity is 58.7% and in the afternoon the temperature of the cage is 30.0 0C and 73.6%. The average respiration frequency of female Balinese cattle in the morning is 21.1 times per minute, while during the day is 24.3 times per minute and in the afternoon is 24.5 times per minute. The average body temperature of female Balinese cattle in the morning is 37.4 0C, during the day is 38.1 0C and in the afternoon is 38.2 0C. The average pulse rate of Bali cattle, in the morning is 60.3 times per minute, during the day is 65.2 times per minute while in the afternoon is 63.7 times per minute. The average rumination in the morning was 55.2 times chewing in 31.9 seconds, during the day the average rumination was 55.3 times chewed in 31.7 seconds while on the afternoon the average rumination was 55, 3 times chew in 31.8 seconds. The physiological status of Bali cattle is respiratory frequency, body temperature, and pulse are in normal conditions. The condition of the ambient temperature exceeds the normal threshold and the rumination in cattle is very high this condition does not cause health problemsÂ Keywords: Bali Cattle, Micro Climate, Physiological Response